Morphological Characteristics of Scoria Cones on the Eastern Part of Slamet Volcano, Karangreja, Purbalingga, Indonesia - Yogi Adi Prasetya; Mohammad Al'afif; Akhmad Khahlil Gibran; Mochammad Aziz (BRIN Publishing, 2026)
Scoria cones are the most common volcanic landforms that are formed by Strombolian eruptions. The Scoria Cones consist of pyroclasts with bomb- and lapilli-sized. In the Karangreja, Purbalingga Regency, these cones are exposed and used for agricultural activities, which has altered their original geomorphology. Despite this extensive modification, the geomorphology of scoria cones in Karangreja, Purbalingga Regency, Central Java, remains poorly studied. This research aims to characterize their external morphology and volcanic landforms through field-based geomorphological analysis, including diameter, height, and degradation processes. This research investigates six scoria cones located in the Karangreja District and surrounding area, on the eastern flanks of Slamet Volcano. Field observations, supported by Digital Elevation Model (DEM) analysis of Shuttle Radar Topography Mission (SRTM) data, were used to characterize their morphology, preservation state, and spatial distribution, and to classify them for geomorphological maps using the van Zuidam classification. The research location is divided into nine geomorphology units: V1, V2, V3, V4, V5, V6, V7, V9, and V12. The studied cones are grouped into V2 and V3. Mt. Asuringkuk, Mt. Kondang, Mt. Lompong, Mt. Tampingan, Mt. Dipajaya, and Mt. Malang feature a variety of morphologies, from very deteriorated forms altered by erosion and agricultural activity to well-preserved, steep-sided cones with distinct craters. The preservation classification reveals a range of states: Asuringkuk and Tampingan occupy intermediate stages, while Dipajaya and Lompong show extensive degradation, while Malang and Kondang represent comparatively newer and well-preserved cones. These variances reflect changes in anthropogenic modification, erosion, and eruptive age. The findings provide information on Slamet's volcanic past and on the establishment of monogenetic volcanic fields in subduction-related environments by demonstrating that the Karangreja scoria cones retain traces of multiple eruptive episodes and subsequent landscape change.